The Role of Geopolymer Concrete in Achieving Sustainable Development Goals - Wibowo, Kevin Aprilio; Widjajakusuma, Jack (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2025)
A sense of safety and comfort is a fundamental right for all people. The United Nations strives to fulfil this through the establishment of 17 Sustainable Development Goals (SDGs). The construction sector plays a significant role in achieving these goals, particularly in the areas of Good Health and Well-being, Clean Water and Sanitation, Decent Work and Economic Growth, Sustainable Cities and Communities, Responsible Consumption and Production, and Climate Action. One key effort in the construction sector is replacing Portland cement with pozzolanic materials. Cement production emits large amounts of carbon dioxide, contributing substantially to global warming. To address this, pozzolanic materials such as fly ash are used as a substitute for cement in the production of geopolymer concrete. Based on compressive strength tests on cylindrical specimens and flexural strength tests on beam specimens, geopolymer concrete demonstrates high potential for structural applications. Its mechanical performance is comparable to that of conventional concrete, making it a promising alternative that supports sustainable development in the construction industry.